PERAN BADAN KEAMANAN DESA DALAM PENGAMANAN DAN PENERTIBAN PADA MASA PANDEMI COVID-19 DI DESA WISATA HIJAU BILEBANTE KECAMATAN PRINGGARATA KABUPATEN LOMBOK TENGAH - Aldi Gumuruh Wicaksono; Rifal Ismail (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
One of the Covid-19 pandemic impacts is an increase of the crime rate. Central Lombok Regency is an area that is prone to criminal acts. One of the policies issued by the Central Lombok Regional Government to reduce the high crime rate is by issuing the Central Lombok Regent Regulation Number 20.A of 2016 concerning Guidelines for the Establishment of a Village/Kelurahan Security Agency. This study aims to determine the role of the Village Security Agency in Securing and Controlling the Bilebante Green Tourism Village during the Covid-19 Pandemic. The method used in this research is descriptive qualitative with an inductive approach. The Bilebante BKD had not carried out its role optimally. The cause is the factor of human resources, inadequate supporting facilities and infrastructure, low levels of welfare and not yet available Security Standard Operating Procedures (SOP). Efforts that can be made to optimize the function of the BKD and create security and order in the village of Bilebante are to conduct a clear and transparent pattern of recruitment of BKD members and involve the participation of the community, provide adequate facilities and infrastructure, increase the operational costs of the BKD and provide a decent salary and preparation of village security SOPs by coordinating with three other village security pillars. Keywords: BKD Bilebante, Crime, Security and Order